Exploring Social Capital within Interreligious Practices in Indonesia - Fitrianita, Titi (Religió Jurnal Studi Agama-agama, 2025)
This article explores the relationship between social capital and interreligious practices in Indonesia. Most discussions of interreligious practices in Indonesia focus on how they directly contribute to discussions of tolerance and peace. Although this is not entirely wrong, the causal relationship between the two is not direct, but through a social process. Therefore, further analysis is needed, especially to unravel the social processes that cause interreligious practices to correlate with tolerance in peace. In interreligious practices, social capital has not yet been explored. This article focuses on finding answers to two main questions: first, what are the different forms of interreligious dialogue in Indonesia, and second, how can interreligious practices contribute to social capital formation in Indonesia. This study, conducted through a comprehensive literature review, shows that religious believers in Indonesia engage in several types of interreligious practices that actively shape their lives. The different practices, undertaken by various actors in all regions of Indonesia and pursued collectively, consistently, and simultaneously, foster bridging social capital that serves as a strong defense against religious conflicts in Indonesia, either by preventing them or reducing their impact.